The Factors Associated with Inaccurate Inpatient Diagnosis Code at Health Information System Ibnu Sina Hospital Gresik Regency - Hasan, Khumaidah; Santi , Maya Weka; Rachmawati , Ervina; Setiawan, Dony (International Journal of Healthcare and Information Technology, 2024)
Inaccuracies in disease diagnosis codes result in inaccurate reports. The results of the preliminary study showed a high rate of code inaccurate (73%). The research aimed to determine the relationship between ability, leadership, reward, motivation and attitude factors on inaccurate inpatient diagnosis codes at HIS Ibnu Sina Hospital, Gresik Regency. This research method uses a cross-sectional approach with the chi-square test. The population used was nurses who coded diagnoses as many as 42 people with a sample of 39 people. The results of observations of inaccurate inpatient diagnosis codes at HIS Ibnu Sina Hospital, Gresik Regency were 49% inaccurate. The results of the attitude factor analysis have a relationship with the inaccurate of inpatient diagnosis codes with P value 0.00 < α (0.05), while the Ability, Leadership, Reward, and Motivation there is no significant relationship with inaccurate inpatient diagnosis codes with P value > α (0.05) at Hospital Information System Ibnu Sina Regional Hospital, Gresik Regency. The suggestion this research is the Hospital Director needs to create a policy regarding the diagnosis input must be carried out by medical recorders, a clear reward and punishment mechanism, monitoring and evaluation by audit team for the number of inaccurate disease diagnosis codes